Can variation in standard metabolic rate explain context‐dependent performance of farmed Atlantic salmon offspring?. Issue 1 (26th December 2018) - Robertsen, Grethe; Reid, Donald; Einum, Sigurd; Aronsen, Tonje; Fleming, Ian A.; Sundt‐Hansen, Line E.; Karlsson, Sten; Kvingedal, Eli; Ugedal, Ola; Hindar, Kjetil
Abstract: Escaped farmed Atlantic salmon interbreed with wild Atlantic salmon, leaving offspring that often have lower success in nature than pure wild salmon. On top of this, presence of farmed salmon descendants can impair production of wild‐type recruits. We hypothesize that both these effects connect with farmed salmon having acquired higher standard metabolic rates (SMR, the energetic cost of self‐maintenance) during domestication. Fitness‐related advantages of phenotypic traits associated with both high SMR and farmed salmon (e.g., social dominance) depend on environmental conditions, such as food availability. We hypothesize that farmed offspring have an advantage at high food availability due to, for example, dominance behavior but suffer increased risks of starvation when food is scarce because this behavior is energy‐demanding. To test these hypotheses, we first compare embryo SMR of pure farmed, farmed‐wild hybrids and pure wild offspring. Next, we test early‐life performance (in terms of survival and growth) of hybrids relative to that of their wild half‐siblings, as well as their competitive abilities, in semi‐natural conditions of high and low food availability. Finally, we test how SMR affects early‐life performance at high and low food availability. We find inconclusive support for the hypothesis that domestication has induced increased SMR. Further, wild and hybrid juveniles had similar survival and growth in the semi‐natural streams. Yet, the presence of hybrids led to decreased survival of their wild half‐siblings. Contrary to our hypothesis about context‐dependency, these effects were not modified by food availability. However, wild juveniles with high SMR had decreased survival when food was scarce, but there was no such effect at high food availability. This study provides further proof that farmed salmon introgression may compromise the viability of wild salmon populations. We cannot, however, conclude that this is connected to alterations in the metabolic phenotype of farmed salmon. Abstract : We demonstrate that presence of hybrids between domesticated and wild Atlantic salmon can lead to decreased early survival of their wild half‐siblings under controlled semi‐natural conditions. This effect was not modified by food availability. Wild Atlantic salmon juveniles from families with high standard metabolic rate had decreased survival when food was scarce, but there was no such effect when food was provided in excess.